The Influence Of Entrepreneur Ability, Work Climate, And Work Motivation On Organizational Commitment Of Private Madrasah Aliyah Teachers In North Sumatra Province - Nasution, Rosida Hanum; Wijaya, Candra; Ananda, Rusydi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to determine the influence of teacher Entrepreneurial Capabilities and work climate on teacher organizational commitment and work motivation of MAS teachers in North Sumatra Province. Study This was carried out in Private Madrasah Aliyah (MA S) in North Sumatra Province with a population of 162 people and technical taking sample done with technique total sampling. The research results show that, there is positive and significant influence between teachers' entrepreneurial abilities to teacher work climate, namely equal to 0.72 , there is a positive and significant influence between entrepreneurial ability direct to Teacher organizational commitment is 0.27 , there is a positive and significant influence between work motivation to The organizational commitment of MAS teachers who have entrepreneurship is 0.287 or 28.7% , there is a positive and significant influence between work motivation in a way direct to personal work climate of 0.26 , and there is a positive and significant influence between teacher work climate and Teacher organizational commitment is 0.27 or by 27%Â